Sampling plans for spittlebug eggs in pastures of Brachiaria decumbens - Nilakhe, S. S.; Martin, P. B.; Valério, J. R.; Koller, W. W.; Souza Filho, J. A.G. de; Silva, A. A. da (Pesquisa Agropecuaria Brasileira, 2014)
A sampling study of spittlebug eggs in pastures of Brachiaria decumbens was conducted by using a sample unit of 15 x 15 cm. The number of samples required for a certain level of precision was inversely proportional to population density. A crude estimate of number of samples necessary for 10, 15 and 20% of precision were 133,59 and 33, respectively. A study of sampling variation showed that differences between plots were much more important than the block differences; therefore plot to plot variation must be considered while sampling spittlebug eggs. The distribution pattern of numbers of eggs per 225 cm2 of pasture fitted the negative binomial series. The sequential sampling plan presented here would reduce the sampling time over the conventional (fixed sample numbers) sampling.
Keywords: Zulia entreriana; Deois flavopicta; Cercopidae; sampling efficiency; sequential sampling